Interpolation of operators of weak type (ϕ, ϕ) - Peleshenko, Borys; Пелешенко, Борис Гнатович (Pleiades Publishing, 2008)
Considering the measurable and nonnegative functions ϕ on the half-axis [0, ∞) such that ϕ(0) = 0 and ϕ(t) → ∞ as t → ∞, we study the operators of weak type (ϕ, ϕ) that map the classes of ϕ-Lebesgue integrable functions to the space of Lebesgue measurable real functions on ℝn. We prove interpolation theorems for the subadditive operators of weak type (ϕ0, ϕ0) bounded in L ∞(ℝn) and subadditive operators of weak types (ϕ0, ϕ0) and (ϕ1, ϕ1) in L ϕ(ℝ n ) under some assumptions on the nonnegative and increasing functions ϕ(x) on [0, ∞). We also obtain some interpolation theorems for the linear operators of weak type (ϕ0, ϕ0) bounded from L ∞(ℝn) to BMO(ℝ n). For the restrictions of these operators to the set of characteristic functions of Lebesgue measurable sets, we establish some estimates for rearrangements of moduli of their values; deriving a consequence, we obtain a theorem on the boundedness of operators in rearrangement-invariant spaces. Розглядаючи вимірні та невід’ємні функції ϕ на півосі [0, ∞) такі, що ϕ(0) = 0 та ϕ( t ) → ∞ при t → ∞, досліджуємо оператори слабкого типу (ϕ, ϕ), що відобразити класи ϕ-інтегровних функцій за Лебегом у простір вимірних за Лебегом дійсних функцій на ℝ n . Доведено інтерполяційні теореми для субадитивних операторів слабкого типу (ϕ 0 , ϕ 0 ) , обмежених в L∞ (ℝ n ), і субадитивних операторів слабкого типу (ϕ 0 , ϕ 0 ) і (ϕ 1 , ϕ 1 ) в L ϕ (ℝ n ) за деяких припущень щодо невід’ємних і зростаючих функцій ϕ( x ) на [0, ∞). Ми також отримуємо деякі інтерполяційні теореми для лінійних операторів слабкого типу (ϕ 0 , ϕ 0 ), обмежених від L ∞ (ℝ n ) до BMO (ℝ n ). Для обмежень цих операторів на множину характеристичних функцій лебегівських вимірних множин встановлено деякі оцінки перестановок модулів їх значень; виводячи наслідок, отримуємо теорему про обмеженість операторів в інваріантних до перестановки просторах.
Інтерполяція операторів слабкого типу (ф,ф)
Keywords: interpolation of operators; інтерполяція операторів; ϕ-integrable function; ϕ-інтегровна функція; operator of weak type; оператор слабкого типу; operator of weak type rearrangement-invariant space; перегрупово-інваріантний простір; modular inequality; модульна нерівність